2020
DOI: 10.1177/1178633720962809
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of HIV Oral Self-Test Among Men Having Sex With Men and Transgender Population: A Qualitative Investigation From Pune, India

Abstract: Globally HIV-self-test is considered as an important tool to end AIDS. However, several countries, including India, are yet to adopt such a strategy. Against this background, we conducted a qualitative inquiry exploring acceptability of an HIV-oral-self-test (HIVOST) among MSM and TG communities in the district of Pune, India. Discussions were facilitated around an HIVOST kit developed in-country. Most of the participants expressed familiarity with the concept of self-test. They realised that confirmatory diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 19 publications
(30 reference statements)
2
12
0
Order By: Relevance
“…The participants in the current study reported some apprehensions around HIVOST such as accuracy of the results, disposal of kits, and self-harm. These findings were similar to the concerns raised by the MSM and TG populations around in Pune, Maharashtra in India [ 33 ].…”
Section: Discussionsupporting
confidence: 89%
“…The participants in the current study reported some apprehensions around HIVOST such as accuracy of the results, disposal of kits, and self-harm. These findings were similar to the concerns raised by the MSM and TG populations around in Pune, Maharashtra in India [ 33 ].…”
Section: Discussionsupporting
confidence: 89%
“…HIVST doubles HIV testing rates, causes no greater social harm than clinic-based testing, and remains associated with reduced risky sexual behavior among MSM (17,20). While previous HIVST studies largely focused on high-income countries (18)(19)(20) recent evidence shows improved testing coverage within low-to-middle income countries, including in SSA (20)(21)(22)(23)(24)(25)(26)(27). WHO guidelines highlight the importance of engaging community members in creating and delivering HIVST initiatives (17).…”
Section: Introductionmentioning
confidence: 99%
“…In our study, we focused on the effectiveness of oral HIVST kits only among MSM. Evidence has shown that oral HIVST kits are less painful than finger-prick HIVST kits and are more acceptable to KPs for HIV testing [23,24]. We also included the latest evidence in the literature on oral HIVST.…”
Section: Strengths and Limitationsmentioning
confidence: 99%